2018
DOI: 10.1101/444075
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain-wide cellular resolution imaging of Cre transgenic zebrafish lines for functional circuit-mapping

Abstract: Decoding the functional connectivity of the nervous system is facilitated by transgenic methods that express a genetically encoded reporter or effector in specific neurons; however, most transgenic lines show broad spatiotemporal and cell-type expression. Increased specificity can be achieved using intersectional genetic methods which restrict reporter expression to cells that co-express multiple drivers, such as Gal4 and Cre. To facilitate intersectional targeting in zebrafish, we have generated more than 50 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Together with whole brain connectome (Hildebrand et al, 2017), single‐cell transcriptomics profiling of neurons (Raj et al, 2018) and glia (Cosacak et al, 2019; Lange et al, 2020), and knowledge on the identities, morphologies, and long‐range projections of cell populations (Kunst et al, 2019), it is now possible to study the function and development of neuronal networks in an entire vertebrate brain with single cell resolution. Moreover, registration of transgenic and experimental brains on standardized atlases (Kunst et al, 2019; Randlett et al, 2015; Tabor et al, 2019) enables scientists to identify neuronal populations involved in specific behaviors (Haesemeyer, Robson, Li, Schier, & Engert, 2018; Randlett et al, 2015; Wee et al, 2019) or diseases (Thyme et al, 2019) in an unbiased manner. Beside investigations at larval stages, recent studies at juvenile zebrafish (2–5 weeks) showed that this relatively transparent (Fore, Cosacak, Verdugo, Kizil, & Yaksi, 2019) development stage allows non‐invasive imaging (Jetti, Vendrell‐Llopis, & Yaksi, 2014; Vendrell‐Llopis & Yaksi, 2015) and exhibit cognitively demanding behaviors such as learning (Palumbo, Serneels, Pelgrims, & Yaksi, 2019; Valente, Huang, Portugues, & Engert, 2012; Yashina, Tejero‐Cantero, Herz, & Baier, 2019) and social interactions (Dreosti, Lopes, Kampff, & Wilson, 2015; Hinz & de Polavieja, 2017; Larsch & Baier, 2018; Tunbak, Vazquez‐Prada, Ryan, Kampff, & Dreosti, 2020).…”
Section: Open Questions and Opportunitiesmentioning
confidence: 99%
“…Together with whole brain connectome (Hildebrand et al, 2017), single‐cell transcriptomics profiling of neurons (Raj et al, 2018) and glia (Cosacak et al, 2019; Lange et al, 2020), and knowledge on the identities, morphologies, and long‐range projections of cell populations (Kunst et al, 2019), it is now possible to study the function and development of neuronal networks in an entire vertebrate brain with single cell resolution. Moreover, registration of transgenic and experimental brains on standardized atlases (Kunst et al, 2019; Randlett et al, 2015; Tabor et al, 2019) enables scientists to identify neuronal populations involved in specific behaviors (Haesemeyer, Robson, Li, Schier, & Engert, 2018; Randlett et al, 2015; Wee et al, 2019) or diseases (Thyme et al, 2019) in an unbiased manner. Beside investigations at larval stages, recent studies at juvenile zebrafish (2–5 weeks) showed that this relatively transparent (Fore, Cosacak, Verdugo, Kizil, & Yaksi, 2019) development stage allows non‐invasive imaging (Jetti, Vendrell‐Llopis, & Yaksi, 2014; Vendrell‐Llopis & Yaksi, 2015) and exhibit cognitively demanding behaviors such as learning (Palumbo, Serneels, Pelgrims, & Yaksi, 2019; Valente, Huang, Portugues, & Engert, 2012; Yashina, Tejero‐Cantero, Herz, & Baier, 2019) and social interactions (Dreosti, Lopes, Kampff, & Wilson, 2015; Hinz & de Polavieja, 2017; Larsch & Baier, 2018; Tunbak, Vazquez‐Prada, Ryan, Kampff, & Dreosti, 2020).…”
Section: Open Questions and Opportunitiesmentioning
confidence: 99%
“…To identify and quantify the forebrain regions driving habenula, we manually delineated distinct forebrain nuclei using anatomical landmarks that were identified by previous studies in zebrafish 17,[66][67][68][69][70][71][72] and in other teleosts [73][74][75][76][77] (Figures 2E and 2F). To further test whether anatomically identified forebrain regions overlapped with functionally distinct forebrain clusters, we compared those manually delineated forebrain nuclei (Figures S2A and S2B) with k-means functional clusters of ongoing forebrain activity (Figures S2C-S2E).…”
Section: Distinct Forebrain Regions Correlate With Ongoing Habenular Activitymentioning
confidence: 99%
“…Differences in the morphology of samples processed for immunostaining and those processed for in situ hybridization makes it challenging to directly compare the location of labelled populations across samples. To overcome this challenge, we developed a brain registration processing pipeline that uses the Advanced Normalization Tools (ANTs) algorithm to morph brains across experiments into the same coordinate space (Marquart et al, 2019;Tabor et al, 2019). Brain registration is a new but widely adopted approach in the zebrafish neurobiology community (Randlett et al, 2015;Tabor et al, 2019).…”
Section: Brain Registrationmentioning
confidence: 99%